(untitled) (Public Sector Economics - submission site, 2024)
The aim of this study is to assess the technical efficiency of the use of investment resources allocated to municipalities in Cameroon. The data used come from the Special Inter-municipal Equipment and Intervention Fund (FEICOM), the National Participatory Development Programme (PNDP) and the Public Investment Budget (BIP), for the period 2010 to 2020, and the Data Envelopment Analysis (DEA) method. The results shows that the BIP counter has the highest efficiency score, at 1 for the whole period, while the scores of the FEICOM and PNDP windows are 0.896 and 0.857 respectively. Secondly, the pooling of resources from the different windows increases the efficiency score obtained, an average of 0.96 for the whole period, even if the new scores remain lower than those of BIP. These results, which highlight the good performance of the BIP window, justified by the significant learning effects from which this window benefits.